Where Inner and Outer Worlds Meet : Psychosocial Research in the Tradition of George W. Brown - Brown, George W. (George William), 1930-; Harris, Tirril O. (Routlege, 2000)
This volume studies George Brown's work on psychiatric disorder and its relationship to social context.